Mind the (unbridgeable) gaps: a cautionary tale about pseudoscientific distortions and scientific misconceptions in the study of religion - Ambasciano, Leonardo (Method & theory in the study of religion, 2016)
In this paper, I explore two of the most pernicious kinds of scientific distortions and misconceptions pertinent to the study of religion (i.e., pseudoscientific trends focused on allegedly paranormal/supernatural phenomena and discontinuity between human and non-human cognition), arguing that: a) the adherence to the prestigious reputation of Eliadean academic frameworks may still cause grave distortions in the comprehension of relevant scientific fields; b) a reliance on cognition alone does not guarantee ipso facto a more epistemically warranted study of religion; c) an evolutionary and cognitively continuist approach to the study of religion is, instead, the most promising and fundamental scholarly tool to bridge the gap between the humanities and the natural sciences, even though it remains a long-term goal; d) the obsolete language of "aboriginal cultures" as open-air museums for our past is rooted in the aforementioned misconceptions and, though basically flawed, is still very much alive.